1890 Wyo. Terr. Laws, ch. 73, § 96 (codified at Wyo. Rev. Stat. § 5051 (1899)). - (:unkn) unknown (My University, 1890)
Every person, not being a traveler, who shall wear or carry any dirk, pistol, bowie knife, dagger, sword-in-cane, or any other dangerous or deadly weapon concealed, or who shall carry or wear any such weapon openly, with the intent, or avowed purpose, of injuring his fellow-man, shall be fined not more than one hundred dollars
Keywords: CARRY